Impact of Capitalization on the Profitability of Nepalese Commercial Banks - Upreti, Shristi; Balami, Sujata; Patel, Sujata; B. K., Tuphan (Nepalese Journal of Finance, 2024)
This study examines the impact of capitalization on the profitability of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are market capitalization, capital adequacy ratio, total deposit, total loan, book value per share and non-performing loans. The study is based on secondary data of 16 commercial banks with 112 observations for the study period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of capitalization on the profitability of Nepalese commercial banks. The study showed that market capitalization has a positive impact on return on assets and return on equity. It indicates that increase in market capitalization leads to increase in return on assets and return on equity. Similarly, capital adequacy ratio has a positive impact on return on assets and return on equity. It indicates that higher the capital adequacy ratio, higher would be the return on assets and return on equity. Likewise, total deposit has a positive impact on return on assets and return on equity. It indicates that increase in total deposits leads to increase in return on assets and return on equity. Further, total loan has a negative impact on return on assets and return on equity. It indicates that increase in total loans leads to decrease in return on assets and return on equity. In addition, book value per share has a positive impact on return on assets and return on equity. It indicates that higher the book value per share, higher would be the return on assets and return on equity. Moreover, non performing loan has a negative impact on return on assets and return on equity. It indicates that higher the non-performing loan, lower would be the return on assets and return on equity.